Tales More Than Just a Game: Dissecting Roblox as a Popular Culture and Digital Social Transformation - Kusmawan, Jihan Azmi; Arifah, Dinillah; Chitra, Bima Prana (Talenta Publisher, 2026)
This paper explores Roblox as a significant phenomenon within contemporary popular culture, focusing on its widespread influence among Generation Z and Alpha. Roblox is not merely a gaming platform but an expansive digital ecosystem that integrates creativity, social interaction, and economic activity. The study discusses four main factors that illustrate Roblox's role in popular culture: addiction and its cognitive consequences often described as ‘brainrot’, the rise of digital consumerism fueled by the Robux virtual currency, the emergence of cyberculture through customizable avatars that sometimes exhibit inappropriate content, and Roblox's function as a